Reclassifcation of Villalbeto de la Pena—Occurrence of a winonaite-related fragment in a hydrothermally metamorphosed polymict L-chondritic breccia - Bischoff, A.; Dyl, Kathryn; Horstmann, M.; Ziegler, K.; Wimmer, K.; Young, E. (John Wiley & Sons, Inc., 2013)
The Villalbeto de la Peña meteorite that fell in 2004 in Spain was originally classified as a moderately shocked L6 ordinary chondrite. The recognition of fragments within the Villalbeto de la Peña meteorite clearly bears consequences for the previous classification of the rock. The oxygen isotope data clearly show that an exotic eye-catching, black, and plagioclase-(maskelynite)-rich clast is not of L chondrite heritage. Villalbeto de la Peña is, consequently, reclassified as a polymict chondritic breccia. The oxygen isotope data of the clast are more closely related to data for the winonaite Tierra Blanca and the anomalous silicate-bearing iron meteorite LEW 86211 than to the ordinary chondrite groups. The REE-pattern of the bulk inclusion indicates genetic similarities to those of differentiated rocks and their minerals (e.g., lunar anorthosites, eucritic, and winonaitic plagioclases) and points to an igneous origin. The An-content of the plagioclase within the inclusion is increasing from the fragment/host meteorite boundary (approximately An10) toward the interior of the clast (approximately An52). This is accompanied by a successive compositionally controlled transformation of plagioclase into maskelynite by shock. As found for plagioclase, compositions of individual spinels enclosed in plagioclase (maskelynite) also vary from the border toward the interior of the inclusion. In addition, huge variations in oxygen isotope composition were found correlating with distance into the object. The chemical and isotopical profiles observed in the fragment indicate postaccretionary metamorphism under the presence of a volatile phase.